Coupling and interaction between science and technology finance and green development: Based on coupling coordination degree model and panel vector autoregression model - Gao, Chen; Cao, Mingshuo; Wen, Ya; Li, Chenqi (Frontiers in Environmental Science, 2023)
Exploring the coupling and coordination relationship between science and technology finance and green development is the key problem to be solved in achieving high-quality development in China. Based on the coupling coordination degree model and panel vector autoregression (PVAR) model, this paper uses the relevant data from 274 cities in China from 2003 to 2020 to comprehensively evaluate science and technology finance and green development. It empirically analyzes the coordination degree and interaction between the two systems. The results show that: (1) The relationship between science and technology finance and green development has changed from low coupling coordination to medium coupling coordination in the sample period. (2) The Beijing-Tianjin-Hebei, Yangtze River Delta and Pearl River Delta regions are at a relatively high level of coupling and coordination as a whole, while other regions are at a relatively low level of coupling and coordination. (3) Through the analysis of the spatial characteristics of the coupling coordination degree, it is found that the coupling coordination degree of China's urban science and technology finance and green development is generally positive spatial autocorrelation. With time, the spatial correlation continues to strengthen. (4) Science and technology finance, green development and their coupling and coordination affect each other.